Discourse and Disjuncture between the Arts and Higher Education
X, 263 p.
Keywords: This accessible and compelling collection of faculty reflections examines the tensions between the arts and academics and offers interdisciplinary alternatives for higher education. With an eye to teacher training, these artist scholars share insights, models, and personal experience that will engage and inspire educators in a range of post-secondary settings. The authors represent a variety of art forms, perspectives, and purposes for arts inclusive learning ranging from studio work to classroom teaching to urban settings in which the subject is equity and social justice. From the struggles of an arts concentrator at an Ivy League college to the challenge of reconciling the dual identities as artists and arts educators, the issues at hand are candid and compelling. The examples of discourse ranging from the broad stage of arts advocacy to an individual course or program give testimony to the power and promise of the arts in higher education.